Islamic Human Resource Management Practices and Innovation in Malaysian Public Service - Ilhaamie Abdul Ghani Azmi (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
The contribution of Islamic human resource management practices (IHRM) on enhancing innovation has not been researched yet in Malaysian public service. Moreover, one of IHRM practices which is Islamic promotion practice has not been studied in previous researches. Thus, this is the impetus of this study. As many previous studies have engaged quantitative method in attaining their research objectives, this study tries to contribute to the body of knowledge by engaging qualitative method whereby semi-structured interviews are conducted with the top management and exec-utives of ten public agencies. Five interviews are allocated to each awarded and non-awarded public organizations. The purpose is to examine the similarities and differ-ences of these public agencies and between different types of informant. The results found similarities and differences among the awarded and non-awarded public agen-cies. The result shows that majority of the awarded public organizations agreed that the implementation of IHRM practices in the organizations has enhanced innovation. The findings of this study indicate that IHRM practices should continue to be imple-mented in Malaysian public service as it contributes to increasing innovation at the workplace.